Peculiarities of the seasonal variability of the external thermal balance and its components on the surface of the Atlantic Ocean - Artamonov, Yu.V.; Lomakin, P.D.; Skripaleva, E.A.; Timofeev, N.A.; Yurovsky, A.V.; Bulgakov, N.P. (Національний антарктичний науковий центр МОН України, 2004)
The results of the investigations of the peculiarities of spatial distribution and seasonal variability of the external heat budget on the surface of the Atlantic Ocean and its components – net radiation budget and latent and sensible heat fluxes, are presented. It is shown that maximum values of the radiation balance are observed on the tropical peripheries of the subtropical centers of high atmospheric pressure in both hemispheres. Extreme values of the sensible and latent flux are in good correlation well with the wind field parameters in the tropical zone of the ocean and in the area of the Antarctic Circumpolar currents as well as with the characteristics of the meridian large-scale currents. Maximum of seasonal variations of external heat balance are characteristic of the Gulf Stream zone, the western Southern subtropical anticyclonic circulation and the Falkland current area. The study was carried out using up-to-date satellite data sets.